2021
DOI: 10.1080/21655979.2021.2006953
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor is a prognostic biomarker and is correlated with immune responses in cervical cancer

Abstract: Aryl hydrocarbon receptor (AHR) plays an important role in tumor development. However, its function in cervical cancer has not been fully elucidated. We evaluated the ten genes that are predicted to associate with AHR protein interaction. The comprehensive scores were: CYP1A1, ARNT2, HSP90AA1, ARNT, AIP, PTGES3, HSP90AB1, CYP1B1, ESR1, MAF, respectively. In addition, we showed that levels of AHR and its related genes were correlated with the immune infiltration and expression of immuno-regulators (immunoinhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In BRCA, upregulation of PTGES3 was significantly correlated to CD8+ T cell abundance in TME, suggesting that PTGES3 could be an immune regulator. In addition, it was revealed that PTGES3 was negatively associated with immunoinhibitors, immunostimulators, and Major Histocompatibility Complex molecules in cervical cancer [ 43 ]. However, the relationship between PTGES3 expression and immune regulation in LUAD has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In BRCA, upregulation of PTGES3 was significantly correlated to CD8+ T cell abundance in TME, suggesting that PTGES3 could be an immune regulator. In addition, it was revealed that PTGES3 was negatively associated with immunoinhibitors, immunostimulators, and Major Histocompatibility Complex molecules in cervical cancer [ 43 ]. However, the relationship between PTGES3 expression and immune regulation in LUAD has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…TDO is a critical prognostic oncolytic biomarker, as its overexpression correlates with poor overall and progression-free survival [97]. Mechanistically, TDO catabolizes Trp to Kyn, a binding ligand for the aryl hydrocarbon receptor (AHR), which is involved in multiple bioregulatory processes contributing to CC progression [98,99]. Details of the AHR pathway and its role in cancer progression are beyond the scope of this review but are extensively discussed elsewhere [100,101].…”
Section: Immunopathogenesismentioning
confidence: 99%